Efficacy and intrarenal pressure analysis of flexible and navigable suction ureteral access sheaths with flexible ureteroscopy in modified surgical positions for 2–6 cm upper urinary tract stones: a multicenter retrospective study - Bai, Junjie; Shangguan, Tong; Zou, Gaoyu; Liu, Liangguang; Xue, Xiyun; Lin, Jun; Ye, Yushi; Ruan, Xiuwu; Li, Yongbin; Yang, Shengzeng; Chi, Yangjian; Nian, Yongqiang; et al. (Frontiers in Medicine, 2024)
This multicenter retrospective study aimed to assess the efficacy, intrarenal pressure (IRP), and complications of retrograde intrarenal surgery (RIRS) using a flexible and navigable suction ureteral access sheaths (FANS-UAS) in the reverse Trendelenburg lithotomy position (RTLP) for treating kidney and upper ureteral stones measuring 2-6 cm. Conducted at six medical centers in Fujian Province from 2022 to 2024, the study included 231 patients with a median stone size of 26 mm. The immediate stone-free rate (ISFR) was 90.48%, while the SFR at postoperative day 30 was 95.67%. Only two patients developed postoperative fever, two patients had ureteral laceration and most experienced mild pain. Although surgical time increased with stone size, factors such as sex, infundibulopelvic angle (IPA), and stone density had little effect on duration, and there was no significant difference between ISFR and 30-day SFR. Importantly, all IRP measurements remained within normal limits. These findings suggest that RIRS with FANS-UAS in RTLP is a safe and effective approach for managing upper urinary tract stones of 2-6 cm.